Structural Configuration and Paleogeography of The “Krishna” Field in The Sunda Basin - Wicaksana, Kharis Surya; Pasaribu, Dumex; Purba, Humbang (Scientific Contributions Oil and Gas, 2025)
The Krishna Field is located in the Sunda Basin and is estimated to have significant hydrocarbon potential. This study aims to analyze the subsurface conditions, geological structure configuration, and paleogeography of the field. The research utilizes 3D seismic data and drilling well data obtained from the Research and Development Center for Oil and Gas Technology “LEMIGAS”. The methodology for this study comprises several stages, namely the preparation stage, which involves a literature review and the process of acquiring supporting data. The data processing stage includes well-seismic tie, well correlation, horizon and fault picking, and the generation of structural and isopach maps. The analysis stage, in which the processed data is analyzed through electrofacies analysis, sequence stratigraphy, seismic stratigraphy, and depositional environment analysis. The results of the study indicate that during the pre-rift phase, the basement rocks were faulted by northeast-southwest trending normal faults with a dominant dip to the southeast, forming a half-graben basin structure. The Talang Akar Formation was deposited in a transitional environment as a syn-rift phase deposit. This was followed by a transgression event, marked by a rise in sea level, where the Baturaja Formation was deposited as a late syn-rift phase deposit, and subsequently followed by the Gumai Formation during the post-rift phase, which has a consistent layer thickness but a more complex and intense structure, deposited in a shallow marine environment.